Literatur Review : Pengetahuan Ibu dan Dukungan Suami dalam Penggunaan Alat Kontrasepsi IUD - Pipit Ariani; Hapsari Windayanti; Asmida Erliana Simatupang; Sri Widyawati; Indawati; Ari Budiawati; Istatik Ulyanita; Delvianti Tandean; Muhdia (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2023)
Increasing population is a problem in every country, including Indonesia. The increasing population must be accompanied by an increase in the number of Family Planning (KB) acceptors. The vision of the National Family Planning Program (KB) is the realization of the Happy Prosperous Small Family Norms (NKKBS). Among the steps taken to achieve the goal of reducing fertility is increasing access to long-term family planning (MKJP) methods such as implants, MOP and MOW, and contraceptive devices (IUD). The aim of this literature review is to determine the relationship between the mother's level of knowledge and husband's support for IUD use. This research uses a systematic review method by analyzing a specified number of articles. This research consists of 24 articles that were reviewed which will be analyzed using article selection techniques, finding 5 articles that meet the criteria in line with the aim of the article. The results of the literature review from these 5 articles show that there is a significant relationship between the husband's level of knowledge and support and the use of IUD contraception. Conclusion, the mother's level of knowledge and husband's support are important factors for wives in making the family planning program successful in using IUD contraception.   Abstrak Peningkatan jumlah penduduk menjadi salah satu masalah di  setiap negara,  termasuk Indonesia. Jumlah penduduk yang    semakin    bertambah    harus    dibarengi dengan meningkatnya jumlah akseptor Keluarga Berencana (KB). Visi Program Keluarga Berencana Nasional (KB) adalah terwujudnya Norma Keluarga Kecil Bahagia Sejahtera (NKKBS). Diantara langkah-langkah yang dilakukan untuk mencapai tujuan penurunan fertilitas adalah peningkatan akses metode keluarga berencana jangka panjang (MKJP) seperti implan, MOP dan MOW, dan alat kontrasepsi (IUD). Tujuan dari literature review ini yaitu untuk mengetahui hubungan antara tingkat pengetahuan ibu dan dukungan suami terhadap penggunaan IUD. Sebanyak 5 artikel yang didapat dari data base Google Schoolar, Arjuna, Garuda dan Sinta dengan kriteria inklusi artikel terbit tahun 2018-2023, bisa diakses full pdf dan kriteria ekslusi tidak bisa diakses full pdf dan merupakan artikel ulasan review. Hasil literature review dari 5 artikel tersebut, menunjukkan bahwa ada hubungan yang siginifikan antara tingkat pengetahuan dan dukungan suami dengan penggunaan kontrasepsi IUD. Kesimpulan, Tingkat pengetahuan ibu dan dukungan suami merupakan faktor yang penting bagi istri dalam mensukseskan program KB dalam penggunaan kontrasepsi   IUD.